2022
DOI: 10.1101/2022.03.07.483334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RUNX1 isoform disequilibrium in the development of trisomy 21 associated myeloid leukemia

Abstract: Aneuploidy is a hallmark of cancer, but its complex nature limits our understanding of how it drives oncogenesis. Gain of chromosome 21 (Hsa21) is among the most frequent aneuploidies in leukemia and is associated with markedly increased leukemia risk. Here, we propose that disequilibrium of the RUNX1 isoforms is key to the pathogenesis of trisomy 21 (i.e. Down syndrome)-associated myeloid leukemia (ML-DS). Hsa21-focused CRISPR-Cas9 screens uncovered a strong and specific RUNX1 dependency in ML-DS. Mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
1
1
0
Order By: Relevance
“…Here, we showed that low-dose BET inhibitor treatment inhibits both proliferation and survival of megakaryoblasts. Our data suggest that the MYC pathway is a major and targetable pathway in DS-AMKL and are consistent with a recent study showing that MYC inhibition induces apoptosis of DS-AMKL blasts ( 46 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we showed that low-dose BET inhibitor treatment inhibits both proliferation and survival of megakaryoblasts. Our data suggest that the MYC pathway is a major and targetable pathway in DS-AMKL and are consistent with a recent study showing that MYC inhibition induces apoptosis of DS-AMKL blasts ( 46 ).…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the SMC3 +/– -dependent gain in RUNX1/ETS binding site accessibility in T21 MKs may synergize with the previously reported loss of interaction between RB1 and GATA1s ( 44 ). An increased level of MYC and of MYC activity in DS-AMKL in comparison with other pediatric AMKL has been previously reported ( 45 ), and recently it has been reported that it is related to an excess of RUNX1A isoform ( 46 ). Here, we showed that low-dose BET inhibitor treatment inhibits both proliferation and survival of megakaryoblasts.…”
Section: Discussionmentioning
confidence: 68%